Multimodality Diagnosis of Laryngeal Cancer in “Dharmais” National Cancer Hospital (DNCH) - Dian Cahyanti; Syahrizal Syarif; Septiawati -; Evlina Suzanna (Indonesian Journal of Cancer, 2023)
Background: Almost 95% of laryngeal cancers are squamous cell carcinoma. Most of them come from the supraglottic and glottic regions. Globally from 1990 to 2017, there was an increase in the incidence of laryngeal cancer by 58.67%. Patients with suggestive grievances of laryngeal cancer symptoms are usually advised to do a further examination. The use of multimodality diagnosis is helpful for the diagnosis of cancer. Diagnostic procedures in diagnosing laryngeal cancer can be made by history and physical examination, clinical (laryngoscopy), and supporting examination (radiology and biopsy). This study aims to determine the distribution of the demographic (gender, age, domicile, marital status, and educational level), clinical distribution (voice changes, respiratory disorders, pain, dizziness, cough, lump on the neck, and others), and modalities of diagnosis (anamnesis, clinical examination, radiology, and biopsy) in laryngeal cancer.Methods: Descriptive study and a routine data-based study was conducted by collecting data on cancer patients who were diagnosed with laryngeal cancer from 2003 to 2007 by the microscopic either in Dharmais National Cancer Hospital (DNCH) or other hospitals. The study sample was 53 out of a total of 68 cases of laryngeal cancer who had been diagnosed with malignancy histopathologically at DNCH or in other hospitals with epithelial or non-epithelial types with completed medical records. Results: The glottic region is the most common subsite, that is, 52.8%, and squamous cell carcinoma (SCC) is the most common histopathological type of laryngeal cancer. In most of the cases, either males or females presented with a change in the voice of 68.8% and 80% respectively. In 6 out of 12 cases have not been examined microscopically before, while 7.5%.of the cases have done the diagnostic procedure completely in DNCH. Conclusions: The most common subsite and histopathological type of laryngeal cancer is glottis and SCC. The most common clinical feature in both sexes is voice changes. Most cases have not been examined according to the standard diagnosis procedure completely.